ANALISIS PENERAPAN PRINSIP GOOD GOVERNANCE DALAM MANAJEMEN KEUANGAN DI YAYASAN BAITUL MAAL HIDAYATULLAH - Syamsid Dluhaa; Novie Andriani Zakariya (ITB Swadharma, 2026)
This study aims to analyze the implementation of good governance principles in financial management at the Baitul Maal Hidayatullah Foundation (BMH), one of Indonesia's national zakat collection institutions. The study focuses on the five main principles of good governance, namely transparency, accountability, responsibility, independence, and fairness in the management of zakat, infaq, sedekah, and waqf funds. The research method uses a qualitative approach with a case study type. The data collection method uses In-depth interviews with BMH administrators, observations of fund management activities, and documentation of financial reports. Data analysis uses the Miles and Huberman model, focusing on data reduction, data presentation, and conclusion. The results show that BMH has attempted to implement good governance principles, especially in transparency, by publishing annual financial reports and ensuring accountability through an internal reporting system. However, several obstacles are faced, including limited independent external audits, differences in human resource capacity across branches, and an inadequate distribution of funds to remote areas. This research provides theoretical contributions to the development of financial management studies for zakat institutions and practical contributions to BMH's efforts to improve financial governance, making it more professional, accountable, and sustainable.Penelitian ini bertujuan untuk menganalisis implementasi prinsip good governance dalam manajemen keuangan di Yayasan Baitul Maal Hidayatullah (BMH) sebagai salah satu lembaga amil zakat nasional di Indonesia. Fokus penelitian diarahkan pada lima prinsip utama tata kelola yang baik, yaitu transparansi, akuntabilitas, responsibilitas, independensi, dan keadilan dalam pengelolaan dana zakat, infak, sedekah, dan wakaf. Metode penelitian menggunakan pendekatan kualitatif dengan jenis studi kasus. Data diperoleh melalui wawancara mendalam dengan pengurus BMH, observasi kegiatan pengelolaan dana, dan dokumentasi laporan keuangan. Analisis data dilakukan menggunakan model Miles dan Huberman melalui reduksi data, penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa BMH telah berupaya menerapkan prinsip good governance khususnya pada aspek transparansi dengan publikasi laporan keuangan tahunan dan akuntabilitas melalui sistem pelaporan internal. Namun demikian, terdapat beberapa kendala yang dihadapi, di antaranya keterbatasan audit eksternal independen, perbedaan kapasitas sumber daya manusia di setiap cabang, serta belum optimalnya pemerataan distribusi dana ke wilayah terpencil. Penelitian ini memberikan kontribusi teoretis dalam pengembangan kajian manajemen keuangan lembaga zakat dan kontribusi praktis bagi BMH untuk meningkatkan tata kelola keuangan yang lebih profesional, akuntabel, dan berkelanjutan.